Assignment of Grammatical Gender in Heritage Greek - Karayiannis, Demetris; Kambanaros, Maria; Grohmann, Kleanthes K.; Alexiadou, Artemis (Frontiers in Psychology, 2021)
This study investigates the acquisition of grammatical gender in Heritage Greek as acquired by children (6–8 years of age) and adolescents (15–18 years) growing up in Adelaide, South Australia. The determiner elicitation task from Varlokosta (2005) was employed to assess the role of phonological and semantic cues when it comes to gender assignment for real and novel nouns. Ralli’s (1994) inflectional classes for Greek nouns and Anastasiadi-Symeonidi & Cheila-Markopoulou’s (2003) categories of prototypicality were employed in the analysis of the collected data. The performance of heritage speakers was compared to that of monolingual speakers from Greece (Varlokosta 2011). The results indicate that—beyond age differences in the two groups—a formal phonological rule guides gender assignment in the production of heritage speakers.